1988
DOI: 10.1002/1097-0142(19880801)62:3<500::aid-cncr2820620310>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of chromosomal aberrations in chronic B-lymphocytic leukemia. A longitudinal cytogenetic study of 41 patients

Abstract: Serial chromosome analyses with a mean of 3.7 samplings during a mean interval of 4.2 years (range, 1.5 to 8.6 years) were performed on B-cell mitogen-activated chronic B-lymphocytic leukemia (CLL) cells from 41 patients. Twenty-four of these patients (59%) had progressive disease. Clonal chromo-somal aberrations were found in 28 patients; 12 had an extra chromosome 12. Thirty patients (73%), 17 with and 13 without clonal aberrations, retained their karyotype throughout the study, although six lost minor subcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Both Cox regression and KaplanMeier analysis indicate that the impact of translocation is not different in UNT or PRT patients. It is worth mentioning, however, that despite the commonly accepted postulate that karyotypes are rather stable in B-CLL over time, 22 other studies have found a higher incidence of karyotypic evolution, including in UNT patients. 23,24 We observed clonal evolution in about 30% of patients.…”
Section: Discussionmentioning
confidence: 96%
“…Both Cox regression and KaplanMeier analysis indicate that the impact of translocation is not different in UNT or PRT patients. It is worth mentioning, however, that despite the commonly accepted postulate that karyotypes are rather stable in B-CLL over time, 22 other studies have found a higher incidence of karyotypic evolution, including in UNT patients. 23,24 We observed clonal evolution in about 30% of patients.…”
Section: Discussionmentioning
confidence: 96%
“…36 It is worth noting that cores for microarray construction were obtained from those areas with PC in the original lymph node section, and that PC may be viewed as a genetically unstable proliferation compartment releasing small lymphocytes in the accumulation compartment and in the PB 14 ; ii) 14q32 translocation may be associated with adenopathy and active disease requiring treatment, as suggested in two recent analyses 9,10 ; and iii) 14q32 translocation may represent in some of our cases a secondary anomaly acquired late during the course of the disease. Indeed, karyotype instability was detected in a fraction of CLL, [37][38][39] and 14q32/ IgH translocation may represent a late event in the progression of lymphoid neoplasias. 40 Interestingly, recent analyses on a limited number of CLL patients reported a 17-21% incidence for these translocations in lymph node samples, 29,41 and 18 independent lymph node biopsies submitted to FISH analysis on isolated cell suspension in this study gave a 33% incidence for this aberration.…”
Section: Discussionmentioning
confidence: 99%
“…However, these timeconsuming metaphase analyses were completely replaced by interphase FISH and fell into oblivion. [6][7][8][9][10][11][12][13] After stimulation with CD40L or CpG-ODN, we are now able to detect chromosomal aberrations in approximately 90% of patients with CLL. In fact, der(2)t(2;16)(p11;p13) [16] der(4)t(2;4)(p21;q13) [16] der (7)t(4;7)(q13;q22) [16] der(13)t(7;13)(q22;q14) [16] der (16) der(1)t(1;6)(q25;p11) [4] der(3)t(3;5)(q21;q13) [4] der (6) der(11)t(4;11)(q11;p13) [2] ins(11;13)(q12;q21q34) [2] der(8)(ins8;15)(p12;qq) [2] der (18) t(4;7)(q23;q11.2) [2] der(4)t(4;7)(q23;q11.2) [2] der(6)t(6;7)(p21;q11.1) [2] der (7) [11] del(13)(q12q14) [11] t(1;15;19)(p36;q15;p11) [11] t(12;14)(q13;q32) [11] der(3)(3;11)(p25;q22) [ [7] del(11)(q13q22) [11] del(13)(q12q22) [7] t(3;6)(p21;p22) [4] t ( t(1;1)(p36;q10) [18] t(10;18)(q21;q21) [18] der (17) t(12;18)(q23;q21) [3] der (17) (1)t(1;6)(q21;?)…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Cytogenetic analyses in CLL were performed in the 1980s evaluating metaphases that were obtained after stimulation with B-cell mitogens such as TPA. [6][7][8][9][10][11][12][13] Although chromosomal aberrations were detected by this approach in 40% to 50% of patients, this technique and its prognostic implications were mostly replaced when interphase fluorescence in situ hybridization (FISH) became available. Nowadays, chromosome analysis is usually performed by interphase FISH using a probe set that, according to our current knowledge, covers regions often involved in numerical or structural rearrangements.…”
Section: Introductionmentioning
confidence: 99%